Competitive Advantage of Common Sense: Using the Power You Already Have, The - O'Connell, Fergus (Financial Times Prentice Hall books., 2003)
Life doesn't have to be so complicated - and neither does business. In The Competitive Advantage of Common Sense , leading project management consultant Fergus O'Connell identifies seven "common sense" principles for supercharging your effectiveness. O'Connell unearths simple root causes underlying the most challenging business problems - and equally simple solutions. From project estimating to working with technical specialists, improving meetings to reducing interruptions, this book offers an arsenal of practical ideas for managers in any business environment.